Genetic diversity and phylogenetic analysis of mayfly Caenis (Insecta: Ephemeroptera) using Cytochrome C Oxidase I (COI) and 12s rRNA genes from Thailand (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Prakrongrak N, Boonsoong B, Monthatong M. 2023. Genetic diversity and phylogenetic analysis of mayfly Caenis (Insecta: Ephemeroptera) using Cytochrome C Oxidase I (COI) and 12s rRNA genes from Thailand. Biodiversitas 24: 1989-1997. Mayflies in genus Caenisis one of the top fifth species richnessbelonged to Family Caenidae. The present study aimed to use the partial mitochondrial Cytochrome COxidase subunit I (COI) and 12s rRNA nucleotide sequences for molecular species identification, diversity and phylogenetic relationships of mayflies in genus Caenis Stephens, 1835 species from Thailand. From a total of 37 specimens, thirteen nymphs were morphologically identified into five species: Caenis nasuta Malzacher, C. Picea Kimmins, C. ulmeriana Malzacher, C. cornigera Kang and Yang and C. longiforcipata Malzacher. The other 24 samples were Caenis sp.1 to sp.5. Partial COI sequences of all samples were compared with BOLD and GenBank for species identification. However, the result showed only genus-level identification as Caenis with greater than 80% similarity. For species delimitation, interspecific genetic distance among these species ranged from 14.4 to 26.6% (COI) and from 7.36 to 22.4% (12s rRNA). Intraspecific divergence levels were 0.0% to 2.35%. ABGD analysis of both genes divided data into 10 groups corresponding to 10 morphospecies of Caenis. The phylogenetic relationships of Caenis, COI and 12s rRNA genes also classified each species to well supported clusters. In addition, we report C. cornigera from Thailand for the first time. The COI and 12s rRNA phylogenetic trees indicate a close relationship between C. cornigera and C. longiforcipata, which is supported by their similar morphology.